(untitled) (Revista Española de Derecho Internacional, 2008)
The Convention on the International Recovery of Child Support and Other Forms of Family Maintenance was adopted within the Hague Conference on Private Intemational Law in November 2007, with the aim of updating the regulation of international support claims, a topic where the existing instruments seemed not to cover the current needs of the global society. The final negotiation of this instrument with occasion of the 21st Diplomatic Session entailed the beginning of a new era because it was the first time the European Community participated as a member of the Organization. This novelty determined the dynamics of the debates the way the present article intends to reflect, focusing on some of the most controversial articles of the Convention.